Jeepers creepers [videorecording (DVD)] - Salva, Victor; Philips, Gina, 1970-; Long, Justin, 1978-; Breck, Jonathan, 1965-; Brennan, Eileen (MGM Home Entertainment, 2002)
Alone on a desolate highway, two homebound teens are nearly run off the road by a demented tailgater. Later they spot this maniac disposing a body down into a sewer pipe. When they stop to investigate, they realize the horrible mistake they have made. The unspeakable evil maniac now intends to make them his next victims.